FORMATION OF CULTURAL AND SPIRITUAL VALUES IN THE MODERN YOUTH ENVIRONMENT - Ryzheva, Nadiya; Marynchenko, Hanna (Sworld-Us Conference proceedings, 2023)
In the contemporary stage of Ukrainian society's development, the worldview foundations of youth in the realm of spiritual realities contribute to an increasing search for cultural and religious orientations. This trend is one of the key characteristics